Assessment Methodology of the Supply Chain Management in Social Entrepreneurship Development at the Macro-regional Level - I.V Takmasheva (International Journal of Supply Chain Management, 2020)
Abstract- Effective supply chain management of the active development process of the social economy requires the use of separate tools to measure the level of social entrepreneurship, including the state of the environment in which enterprises are created. In this regard, the author proposes a method for assessing the level of the social entrepreneurship development in the macro-region. The method of calculating the integrated index of innovative development of the region as the basis of the proposed tools was used and subsequently adapted. The proposed calculation model was adapted to the problem of measuring the level of development of social entrepreneurship by including an expert method for determining the weight coefficients of each thematic block. An evaluation scale was also introduced, which can serve as a basis for making recommendations for consistently improving the level of social entrepreneurship development in the region. The evaluation is calculated in four consecutive stages: collecting the values of each indicator, rationing each indicator included in the evaluation system, calculating the index for each thematic block, and calculating the integral index for the development of social entrepreneurship.